Metáforas conceptuais de tempo, vida, morte na construção colaborativa das leituras de um texto literário - Boas, Gislaine Aparecida de Vilas (2010)
This work is part of a larger project developed by the research group GEIM (Research Group of Indeterminacy and Metaphor) coordinated by Prof. Dr. Mara Sophia Zanotto. To contribute to the development of the group, this study investigates a practice of reading as a social event (Bloome, 1993; Street, 1993) in a real context of language use, with real readers. Therefore, this work fits in the Applied Linguistics, as this area is concerned with the real problems of language use (Celani, 1998; Moita Lopes, 2006). Thus, the objective was to discuss the role of conceptual metaphor (Lakoff & Johnson, 1980) in the process of interpreting a literary text, within a practice of reading in which it admits to making sense of the text by the reader, validating, thus, the multiple readings. Metaphor, under socio-cognitive paradigm, is one of the pillars of the constructions of meaning, so it is essential the discussion of its influence on reading literary texts. The metaphorical concepts structure our thought and therefore have implications in the way of interpreting a text. Thus, it was addressed in this work, the importance of literary texts in the classroom, offering a reading practice to consider the subjectivity of readers, rescuing the pleasure of literary reading. To this end, this work was developed under the current interpretive, a qualitative chain, in which the research instrument used in this work is part of: the Think-Aloud in Group. That tool is now used by the group GEIM also as a pedagogical practice that has shown influence on reading as social practice (Zanotto, 1997, Zanotto & Palma, 2008). Therefore, the Think-Aloud in Group is considered a practice of literacy, for all practical literacy is a social practice (Street, 1993). Thus, when working with this practice, which focuses on the interaction among readers, it was possible to investigate how conceptual metaphors influence the construction of the readings during the interpretation of a literary text into a social event of reading